Associations of depressive and anxiety symptoms with non-suicidal self-injury and suicidal attempt among Chinese adolescents: The mediation role of sleep quality - Jiao, Ting; Guo, Shuangshuang; Zhang, Yi; Li, Yanqi; Xie, Xinyi; Ma, Ying; Chen, Ruoling; Yu, Yizhen; Tang, Jie (Frontiers in Psychiatry, 2022)
Background: Associations of depressive and anxiety symptoms with non-suicidal self-injury (NSSI) and suicide attempt (SA) are not well understood. We aimed to examine these associations among Chinese adolescents, and whether any potential association is mediated through sleep quality. Methods: We conducted a cross-sectional study among 1771 (994 boys [56.1%] and 777 girls [43.9%], mean [SD] age was 12.9 [0.6] years) adolescents who participated in the baseline survey of the Chinese Adolescent Health Growth Cohort (CAHGC) study. Depressive symptoms, anxiety symptoms, NSSI, SA and sleep quality were measured by validated questionnaire. Logistic regression models were employed to estimate the associations of depression and anxiety with NSSI and SA. Mediation analyses were conducted to explore the mediate effect of sleep quality. Results: The 12-month prevalence of NSSI and SA was 17.1% and 8.3%, respectively. Depressive and anxiety symptoms were significantly associated with NSSI (the adjusted odds ratio [aOR] was 1.89 [95%CI 1.34-2.65] for depressive symptoms and 2.84 [95%CI 2.05-3.94] for anxiety symptoms) and SA (the aOR was 3.20 [95%CI 2.03-5.05] for depressive symptoms and 2.98 [95%CI 1.84-4.84] for anxiety symptoms). No significant gender differences were found in the associations. The mediation proportion of sleep quality on the association of depressive and anxiety symptoms with NSSI, as well as depressive and anxiety symptoms with SA were 21.1%, 13.9%, 13.6% and 14.7%, respectively. Conclusions: Independent associations of depressive and anxiety symptoms with NSSI and SA were observed in Chinese adolescents, and there were no significant gender differences in the associations. Moreover, these associations were partially mediated through sleep quality. Targeted interventions for adolescents’ NSSI and SA should focus on those who have depressive and anxiety symptoms, and poor sleep quality.